Targeting increased levels of APP in Down syndrome: Posiphen‐mediated reductions in APP and its products reverse endosomal phenotypes in the Ts65Dn mouse model - Chen, Xu‐Qiao (Alzheimers Dement, 2020)
OBJECTIVE: Recent clinical trials targeting amyloid beta (Aβ) and tau in Alzheimer's disease (AD) have yet to demonstrate efficacy. Reviewing the hypotheses for AD pathogenesis and defining possible links between them may enhance insights into both upstream initiating events and downstream mechanisms, thereby promoting discovery of novel treatments. Evidence that in Down syndrome (DS), a population markedly predisposed to develop early onset AD, increased APP gene dose is necessary for both AD neuropathology and dementia points to normalization of the levels of the amyloid precursor protein (APP) and its products as a route to further define AD pathogenesis and discovering novel treatments. BACKGROUND: AD and DS share several characteristic manifestations. DS is caused by trisomy of whole or part of chromosome 21; this chromosome contains about 233 protein‐coding genes, including APP. Recent evidence points to a defining role for increased expression of the gene for APP and for its 99 amino acid C‐terminal fragment (C99, also known as β‐CTF) in dysregulating the endosomal/lysosomal system. The latter is critical for normal cellular function and in neurons for transmitting neurotrophic signals. NEW/UPDATED HYPOTHESIS: We hypothesize that the increase in APP gene dose in DS initiates a process in which increased levels of full‐length APP (fl‐APP) and its products, including β‐CTF and possibly Aβ peptides (Aβ42 and Aβ40), drive AD pathogenesis through an endosome‐dependent mechanism(s), which compromises transport of neurotrophic signals. To test this hypothesis, we carried out studies in the Ts65Dn mouse model of DS and examined the effects of Posiphen, an orally available small molecule shown in prior studies to reduce fl‐APP. In vitro, Posiphen lowered fl‐APP and its C‐terminal fragments, reversed Rab5 hyperactivation and early endosome enlargement, and restored retrograde transport of neurotrophin signaling. In vivo, Posiphen treatment (50 mg/kg/d, 26 days, intraperitoneal [i.p.]) of Ts65Dn mice was well tolerated and demonstrated no adverse effects in behavior. Treatment resulted in normalization of the levels of fl‐APP, C‐terminal fragments and small reductions in Aβ species, restoration to normal levels of Rab5 activity, reduced phosphorylated tau (p‐tau), and reversed deficits in TrkB (tropomyosin receptor kinase B) activation and in the Akt (protein kinase B [PKB]), ERK (extracellular signal‐regulated kinase), and CREB (cAMP response element–binding protein) signaling pathways. Remarkably, Posiphen treatment also restored the level of choline acetyltransferase protein to 2N levels. These findings support the APP gene dose hypothesis, point to the need for additional studies to explore the mechanisms by which increased APP gene expression acts to increase the risk for AD in DS, and to possible utility of treatments to normalize the levels of APP and its products for preventing AD in those with DS. MAJOR CHALLENGES FOR THE HYPOTHESIS: Important unanswered questions are: (1) When should one intervene in those with DS; (2) would an APP‐based strategy have untoward consequences on possible adaptive changes induced by chronically increased APP gene dose; (3) do other genes present on chromosome 21, or on other chromosomes whose expression is dysregulated in DS, contribute to AD pathogenesis; and (4) can one model strategies that combine the use of an APP‐based treatment with those directed at other AD phenotypes including p‐tau and inflammation. LINKAGE TO OTHER MAJOR THEORIES: The APP gene dose hypothesis interfaces with the amyloid cascade hypothesis of AD as well as with the genetic and cell biological observations that support it. Moreover, upregulation of fl‐APP protein and products may drive downstream events that dysregulate tau homeostasis and inflammatory responses that contribute to propagation of AD pathogenesis.